Investigating Vα7.2+/CD161− T Cell and MAIT Cell Profiles Using Flow Cytometry in Healthy Subjects and Subjects with Atopic Dermatitis - Singh, Parvind; Gaspar, Krisztian; Szegedi, Andrea; Sajtos, Laszlo; Barath, Sandor; Hevessy, Zsuzsanna (International journal of molecular sciences, 2024)
This study investigates the roles of mucosal-associated invariant T (MAIT) cells and Vα7.2+/CD161− T cells in skin diseases, focusing on atopic dermatitis. MAIT cells, crucial for bridging innate and adaptive immunity, were analyzed alongside Vα7.2+/CD161− T cells in peripheral blood samples from 14 atopic dermatitis patients and 10 healthy controls. Flow cytometry and machine learning algorithms were employed for a comprehensive analysis. The results indicate a significant decrease in MAIT cells and CD69 subsets in atopic dermatitis, coupled with elevated CD38 and polyfunctional MAIT cells producing TNFα and Granzyme B (TNFα+/GzB+). Vα7.2+/CD161− T cells in atopic dermatitis exhibited a decrease in CD8 and IFNγ-producing subsets but an increase in CD38 activated and IL-22-producing subsets. These results highlight the distinctive features of MAIT cells and Vα7.2+/CD161− T cells and their different roles in the pathogenesis of atopic dermatitis and provide insights into their potential roles in immune-mediated skin diseases.